Numerical methods for solving Sylvester's equation - Kadraoui, Manal; Abdesselam, Nawal (Laghouat : Université Amar Telidji - Département de mathématiques, 2023)
The objective of this work is to solve the Sylvester equation, which plays an important role in the construction of the observer of Luenberger and also in the theory of control, communication, reduction models and numerical methods for the resolution differential equations.
Méthodes numériques pour la résolution de l’équation de Sylveste